Impact of Medical Treatments for Male Lower Urinary Tract Symptoms Due to Benign Prostatic Hyperplasia on Ejaculatory Function: A Systematic Review and Meta‐Analysis. (1st June 2014) - Gacci, Mauro; Ficarra, Vincenzo; Sebastianelli, Arcangelo; Corona, Giovanni; Serni, Sergio; Shariat, Shahrokh F.; Maggi, Mario; Zattoni, Filiberto; Carini, Marco; Novara, Giacomo
Abstract: Introduction: Several drugs, currently used to treat lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH), can be associated with bothersome sexual side effects, including ejaculatory dysfunction (EjD). Aim: To provide a systematic review and meta‐analysis of the available randomized clinical trials (RCTs) reporting the impact of medical treatments for LUTS due to BPH on ejaculatory function. Main Outcome Measure: EjD related to medical treatments for LUTS. Methods: A systematic literature search was performed using PubMed, Scopus and Cochrane databases. EjD was identified using both free text ("ejaculat*, " "retrograde ejaculation, " "anejaculation, " "ejaculatory dysfunction") and Mesh ("Ejaculation") searches. Results: Of 101 retrieved articles, 23 were included in the present meta‐analysis. EjD was significantly more common with alpha‐blockers (ABs) than with placebo (OR:5.88; P < 0.0001), in particular, considering Tamsulosin (OR:8.58; P = 0.006) or Silodosin (OR:32.5; P < 0.0001), with Tamsulosin associated with significantly lower risk of EjD than Silodosin (OR:0.09; P < 0.00001). Conversely, Doxazosin and Terazosin were associated with a risk similar to placebo. Meta‐regression showed that EjD was associated with IPSS and with Qmax both before and after treatment with ABs, while multivariate analysis demonstrated that EjD was independently associated with the improvement of IPSS (adj.r:0.2012; P < 0.0001) and Qmax (adj.r:0.522; P < 0.0001). EjD was significantly more common with 5ARIs as compared with placebo (OR:2.73; P < 0.0001). Both Finasteride (OR 2.70; P < 0.0001) and Dutasteride (OR 2.81; P = 0.0002) were associated with significantly higher risk of EjD than placebo. EjD was significantly more common with combination therapy as compared with ABs alone (OR:3.75; P < 0.0001), or with 5ARIs alone (OR:2.76; P = 0.02). Conclusions: ABs and 5ARI were both associated with significantly higher risk of EjD than placebo. More the AB is effective over time, greater is the incidence of EjD. Finasteride has the same risk of Dutasteride to cause EjD. Combination therapy with ABs and 5ARIs resulted in a 3‐fold increased risk of EjD as compared with ABs or 5ARIs alone. These data can be relevant both for drug selection and patients counseling.